ANALYSIS OF MARKETING ASPECTS IN LAYING CHICKEN FARMING BUSINESS IN THE CASE OF HANIF FARM IN LUBOK SUKON VILLAGE, INGIN JAYA DISTRICT, ACEH BESAR REGENCY - Sara Mustaqilla; Dedhi Yustendi; Mulyadi; Zulkifli (CV Naskah Aceh, 2026)
This study aims to analyze the financial feasibility and marketing strategy of Hanif Farm's egg-laying chicken farming business located in Lubuk Sukon Village, Ingin Jaya District, Aceh Besar Regency. The research method used is a quantitative approach for financial analysis and qualitative-descriptive for marketing analysis. All members of the population were sampled (census). Primary data were obtained through interviews and observations, while secondary data were obtained from financial records and business documentation. The results show that financially, Hanif Farm's business is very feasible and profitable. This is evidenced by the monthly net profit of Rp. 8,583,333.00. Break Even Point (BEP) analysis in units shows the break-even point at 2,081 eggs, which falls lower than the monthly production volume. Furthermore, the Revenue Cost Ratio (R/C Ratio) value is Rp 1.29 per income. In the marketing aspect, the strategy implemented is still traditional, with the main strengths being product quality and word-of-mouth promotion. Weaknesses identified are dependence on collectors, which limits market reach and profit optimization. Based on the SWOT analysis, there is a significant opportunity to expand the market by leveraging simple digital promotions. In conclusion, Hanif Farm is a profitable business, but it needs to diversify its distribution channels and begin implementing digital marketing to boost business growth.